Apocalypse of the Thirteenth Century: the First Russian Encounter with the Mongols through the Prism of the Medieval Mind - Veselov F.N. (Золотоордынское обозрение)
Abstract: Research objective: The idea has already been expressed that the eschatological image of the Mongols of Russian annalists, recorded in the Tale of the Battle on the Kalka River of 1223, after some time, through the reports of Dominican Julian and testimony of Archbishop Peter at the Council of Lyons in 1245, influenced the apocalyptic character of the Mongols’ Great Western Campaign in Latin Europe. However, it remains unstudied why the Russians turned to the terrifying eschatological apocrypha. In the presented study we are going to deal with this question. Research materials: The research is based on a wide range of published original and translated sources of the thirteenth–fourteenth centuries, written in Russian, Latin, French, Arabic, Persian, Syriac and Armenian, as well as the opinions of scholars expressed in literature on related fields. Results and the novelty of research: The appeal of Russian chroniclers to eschatological apocrypha is extremely rare. Before the Tale of the Battle on Kalka, the chronicler refers to the Revelations of Pseudo-Methodius only once, in a chronicle entry about the plundering of Kiev monasteries by the Cumans in 1096. Comparison of these messages, the historical background of the described events, evidence of literary texts, travel reports, chronicles and diplomatic material shows that the Russian writers took upon themselves the responsibility to make a comparison with the Last Times only when a complex of causes formed such a mosaic that it left no other explanation. At the same time, the most important role in the eschatological character of the Tale of the Battle on Kalka was not only caused by the bitterness of the defeat, the demise of many princes and warriors and the desolation of Novgorod Svyatopolchich, but also by the diplomatic rhetoric carried by the Mongol conquerors “from sea to sea”, the warlords of the khan and the people who came from the deep depths of Inner Asia to rule the whole world.